Evaluation of the Respect of the Root Canal Trajectory by Rotary Niti Instruments (Protaper®Universal): A Retrospective Radiographic Study - El Abbassi, Salma; Chala , Sanaa; Sakout , Majid; Abdallaoui , Faïza (Integrative Journal of Medical Sciences, 2022)
Introduction: Root canal shaping is the critical step in endodontic therapy. Perioperative errors, such as false canal stripping, may occur during this step. The endodontic instrumentation based on stainless steel is often the cause of these errors because of the rigidity of the alloy on which it is manufactured. Unlike the endodontic NiTi instrumentation, this allowed better respect of the root canal path, thanks to the flexibility of the NiTi alloy. Materials and Methods: This study aimed to assess the respect of the root canal path by the rotary NITI instruments of the ProTaper® Universal system. This is a retrospective radiological study of 241 canals whose shaping was performed by the rotary ProTaper® Universal system in the Department of Conservative Dentistry & Endodontics at the Dental Treatment and Consultation Center (CCTD), CHIS, Rabat. Results: We noted the occurrence of preoperative incidents at various percentages. The incidence rates were as follows: the ledge with an incidence rate of 3.3%, the false canal with 2.1%, and the stripping with 5.4%; however, zipping had an incidence rate of 1.7%. We also determined a relationship between stripping and a tight preoperative root canal angle. Conclusion: All results suggest the reproducibility of the rotating ProTaper® Universal system.